Visual analysis of diversity and threat status of natural materials for musical instruments - Kusnick, Jakob; Lichtenberg, Silke; Wiegreffe, Daniel; Huber-Sannwald, Elisabeth; Nehren, Udo; Jänicke, Stefan (Frontiers in Environmental Science, 2024)
A classical symphony orchestra consists of up to 29 musical instruments manufactured from up to 758 distinct natural materials. The interrelationships between the extraction of raw materials for instrument making, the international trade conditions, and the protection status of endangered species and their ecosystems are highly complex and have yet to be sufficiently scientifically examined. However, rapidly progressing climate and ecological change call for sustainable solutions. To address this challenging task, we present MusEcology, a new interactive decision support system based on visualizations. The interactive visualizations offer entry points for users of various backgrounds to explore the interrelationships between musical instruments, natural resources and ecosystems. The tool’s fundamental objectives are to guarantee that the (1) data processing correlates related data resources, that (2) visual interfaces and interaction schemes encourage new interdisciplinary research on complex systems interactions, and that (3) high-level decision-making is supported to identify alternative pathways towards sustainable instrument making.